Indonesian MSMEs’ Differentiation Strategy: Enhancing The Mediation Role of Innovation, Accounting Information System and Social Media to Increase Financial Performance - Febrianti, Nurfitasari (Innovation, Technology, and Entrepreneurship Journal, 2025)
This study aims to determine the effect of differentiation strategy on MSME financial performance media by innovation, accounting information systems, and social media. This research technique sampling is purposive sampling and data analysis techniques using Structural Equation Modeling-Partial Least Square (SEM-PLS). The data collection techniques used are quantitative by distributing questionnaires to the MSME actors who are in the city of Surakarta so that the number of Surakarta the sample obtained was 104 MSMEs. The results of this study prove that differentiation strategy has a positive effect on innovation, accounting information systems, and social media. Differentiation strategy has a negative effect on MSME financial performance. Innovation and accounting information systems have a positive effect on MSME financial performance. Social media does not affect MSME’s financial performance. Differentiation strategy has a positive effect on MSME financial performance mediated by innovation, accounting information systems, and social media.